The influence of colour contrast in packaging on consumer behaviour - Witkowska, Zuzanna Anna (2019)
Marketers and package designers have been wondering how to combine colours in order to create positive aesthetics feelings towards a product. The main purpose of this paper is to study the impact of colour contrast in packaging on consumer behaviour, for both complementary and analogous colours, in two different product categories: cookies and milk. To examine this relationship, the following measures were applied: purchase intent, product attractiveness, healthfulness and calories perception. Two experimental studies collected via an online questionnaire show that packaging with contrast of analogous colours is perceived as more likely to be purchased and as more attractive, healthier and less caloric than packaging with complementary colours. We identify that there are differences across specific colour conditions, which highlights the need for exploration of colour interactions. Finally, this paper provides theoretical and marketing implications not only for package designers, but also for marketers in food industry.